2018
DOI: 10.1016/j.mayocpiqo.2018.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Innovative Informatics Approaches for Peripheral Artery Disease: Current State and Provider Survey of Strategies for Improving Guideline-Based Care

Abstract: Objective To quantify compliance with guideline recommendations for secondary prevention in peripheral artery disease (PAD) using natural language processing (NLP) tools deployed to an electronic health record (EHR) and investigate provider opinions regarding clinical decision support (CDS) to promote improved implementation of these strategies. Patients and Methods Natural language processing was used for automated identification of moderate to severe PAD cases from narrative clinical notes of an EHR of pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 27 publications
0
12
1
Order By: Relevance
“…In comparison to other similar studies, the provider survey response rate of 35.8% (100 of 279) was greater than the response rate of 27% (207 of 760) reported by Chaudhry et al 14 investigating provider opinions about CDS for provision of evidence-based care to patients with peripheral artery disease at the point-of-care. Additionally, the response rate of the study herein was greater than the reported rates of 10% (10 of 100) to 15% (15 of 100) from a random sample of physicians across specialties (primary care, obstetrics/gynecology, and cardiology) in a national survey of guideline-recommended strategies for cardiovascular disease prevention.…”
Section: Discussioncontrasting
confidence: 58%
“…In comparison to other similar studies, the provider survey response rate of 35.8% (100 of 279) was greater than the response rate of 27% (207 of 760) reported by Chaudhry et al 14 investigating provider opinions about CDS for provision of evidence-based care to patients with peripheral artery disease at the point-of-care. Additionally, the response rate of the study herein was greater than the reported rates of 10% (10 of 100) to 15% (15 of 100) from a random sample of physicians across specialties (primary care, obstetrics/gynecology, and cardiology) in a national survey of guideline-recommended strategies for cardiovascular disease prevention.…”
Section: Discussioncontrasting
confidence: 58%
“…The majority of the 90 included studies (68/90, 76%) investigated the use of AI in relation to a specific medical condition. Conditions studied were vascular diseases including hypertension, hypercholesteremia, peripheral arterial disease, and congestive heart failure (10/90, 11%) [ 40 - 49 ]; infectious diseases including influenza, herpes zoster, tuberculosis, urinary tract infections, and subcutaneous infections (8/90, 9%) [ 50 - 57 ]; type 2 diabetes (5/90, 6%) [ 58 - 62 ]; respiratory disorders including chronic obstructive pulmonary disease and asthma (6/90, 8%) [ 63 - 69 ]; orthopedic disorders including rheumatoid arthritis, gout, and lower back pain (5/90, 5%) [ 36 , 39 , 70 - 72 ]; neurological disorders including stroke, Parkinson disease, Alzheimer disease [ 73 - 75 ], and cognitive impairments (6/90, 5%) [ 76 , 77 ]; cancer including colorectal cancer, and head and neck cancer (4/90, 4%) [ 78 - 81 ]; psychological disorders including depression and schizophrenia (3/90, 3%) [ 82 - 84 ]; diabetic retinopathy (3/90, 3%) [ 85 - 87 ]; suicidal ideations (2/90, 2%) [ 88 , 89 ]; tropical diseases including malaria (2/90, 2%) [ 90 , 91 ]; renal disorders (2/90, 2%) [ 92 , 93 ]; autism spectrum disorder (2/90, 2%) [ 94 , 95 ]; venous disorders including deep vein thrombosis and venous ulcers (2/90, 2%) [ 96 , 97 ]; and other health conditions (8/90, 8%) [ 98 - 105 ].…”
Section: Resultsmentioning
confidence: 99%
“…The idea of understanding the segmentation first is to solve the lack of global information in the traditional matching segmentation, while the statistical method lacks the structural information of the sentence [36]- [39]. Relevant scholars use deep learning to perform sequence labeling in the NLP field [40], [41]. It can also add a sequence labeling model to combine with the output of the previous neural network to extract the best labeling sequence through the Viterbi algorithm.…”
Section: Introductionmentioning
confidence: 99%